Words, imagery, and the mystery of Christ : a reconstruction of Cyril of Alexandria's christology - McKinion, Steven A. (Vigiliae Christianae, Supplements, 2000)
This volume deals with the christology of fifth-century pastor and theologian Cyril of Alexandria, particularly as it relates to Apollinarianism and Nestorianism. More specifically, it explores the use of a plethora of images to illustrate his understanding of the mystery of Christ. The book traces the background of his analogies in the philosophers and the Scriptures. Included are sections on Cyril's understanding and use of the Scriptures, and the intended force of images in his theology. The final part is a re-reading of his christology through the lens of his christological imagery. Historians of Christian theology and dogma will find a unique look into the word pictures Cyril uses and the picture of Christ the reveal.